1988
DOI: 10.1016/0014-5793(88)80777-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of N‐linked oligosaccharides attached to human renin expressed in COS cells

Abstract: One or both of two putative N-glycosylation sites (at asparagine-5 and -75) of human renin was eliminated by amino acid replacement of the asparagine residue with an alanine residue using site-directed mutagenesis. The three glycosylation-deficient renins (Asn-5, Asn-75, Asn-5 and -75 mutants) were expressed in COS cells and secreted into the conditioned media. The secreted amounts of the three mutants were different from one another, although the mutant and wildtype renins had practically the same specific ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…4A), and the conserved presence of a well defined glycosylation site in a similar region of these three aspartic proteinases might indicate a common biological role. It is possible that they protect these hydrolases against accelerated proteolytic cleavage and therefore play a role in the stability of the enzymes, similar to what was found for recombinant renin expressed in COS cells (47) or for Mucor aspartic proteinase expressed in yeast (48).…”
Section: Resultsmentioning
confidence: 84%
“…4A), and the conserved presence of a well defined glycosylation site in a similar region of these three aspartic proteinases might indicate a common biological role. It is possible that they protect these hydrolases against accelerated proteolytic cleavage and therefore play a role in the stability of the enzymes, similar to what was found for recombinant renin expressed in COS cells (47) or for Mucor aspartic proteinase expressed in yeast (48).…”
Section: Resultsmentioning
confidence: 84%
“…Thus, it appears that N‐glycosylation does not play an essential role for the activity of the plant aspartic proteinases as the sites of addition of N‐glycans are not conserved in the different proteins. Glycosylation of human renin expressed in monkey cells improved the stability of the protein [33] suggesting another potential function of this modification in the plant enzymes. Thus, we obtained protein sequence from the aspartic proteinase purified from seeds [21] that showed that this enzyme was derived from the AtPasp A1 and A2 genes.…”
Section: The Seed Proteinase Is Derived From Two Of These Genesmentioning
confidence: 99%
“…We have recently reported that the glycosylation-deficient human renin (NA575) is unstable m monkey kidney COS cells transfected with its expression plasmid [25]. In this study, we demonstrated that glycosylation of renin plays a pivotal role in its intracellular sorting in oocytes, probably due to its phosphorylation by UDP-GlcNAc: lysosomal enzyme N-acetylglucosaminylphosphotransferase.…”
Section: Discussionmentioning
confidence: 76%
“…Site-directed mutagenesis to substitute the asparagine residues of glycosylation sites of human renin was performed as described previously [25]. The mutated cDNA fragment was exchanged with the corresponding one of the plasmid of native human preprorenin.…”
Section: Methodsmentioning
confidence: 99%